Libraries at the forefront of open science : Proceedings of the International 9th Conference on Libraries, Information and Society, ICoLIS 2023, Putrajaya, Malaysia, 20-21 September 2023 - Samsuddin, Samsul Farid (Department of Library and Information Science, Faculty of Arts and Social Sciences, Universiti Malaya and Universiti Malaya Library, 2023)
Organised by: Department of Library and Information Science, Faculty of Arts and Social Sciences, Universiti Malaya and Universiti Malaya Library.